ANALISIS YURIDIS MENGENAI TINDAKAN PENAWARAN SALING MELENGKAPI DALAM PERSEKONGKOLAN TENDER MENURUT UNDANG-UNDANG NOMOR 5 TAHUN 1999 TENTANG LARANGAN PRAKTIK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT - Afdal, Muhammad; Adiasih, Ning (Fakultas Hukum Universitas Trisakti, 2023)
The form of collusion that can fulfill the element of collusion is in the form of leaking bid documents by adjusting and comparing bid documents made between bidders before the submission deadline. In the decisions of the business competition supervisory commission number 25 of 2020 and number 35 of 2020, the commission panel considered that complementary offers were a form of adjusting and comparing bid documents before the submission deadline. the mechanism for prohibiting complementary offers is divided into 2 elements, namely leaking bid documents by adjusting and comparing bid documents carried out between tender participants before the submission deadline.